Numerical Modeling of a Tornado Event at Skala, Lakonia, Peloponnese in September 2015 - Mylonas, M. P.; Nastos, P. T.; Matsangouras, Ioannis T (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
{Towards the evaluation of the thermodynamic characteristics of a high impact tornadic event in Skala Lakonia, southern Peloponnese, in September 21, 2015, Weather Research and Forecasting (AR-WRF) mesoscale model was used. For the particular model setup used in this study, different configurations were pre-tested based on different spatial resolution and parameterization schemes. The current study downscales ECMWF reanalysis initial and boundary conditions to 300 m spatial resolution to assess the convective available potential energy (CAPE), the reflectivity perceived by radar (dBZ) and the energy helicity index (EHI). The validation was conducted using in situ and remote sensing observations of the surrounding area. The results illustrate deep convective activity with CAPE values indicating a strong instability in the region of interest. Furthermore, the model seems to capture well the southwesterly-northeasterly front propagation of the convective initiation of the storm, as well as the troughs that affected the south part of Peloponnese, assessing the pre-frontal nature of the particular tornadic event. Finally, the EHI values demonstrate the tornadic activity in the region of Skala Lakonia, as the model appears to simulate accurately the low pressure system along the east coast of the Lakonia Gulf.}